1996
DOI: 10.1073/pnas.93.17.9073
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic instability during mammary tumor progression using a novel selection-based assay for in vivo mutations in a bacteriophage lambda transgene target.

Abstract: Genetic instability is thought to be responsible for the numerous genotypic changes that occur during neoplastic transformation and metastatic progression. To explore the role of genetic instability at the level of point mutations during mammary tumor development and malignant progression, we combined transgenic mouse models of mutagenesis detection and oncogenesis. Bitransgenic mice were generated that carried both a bacteriophage A transgene to assay mutagenesis and a polyomavirus middle T oncogene, mammary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
191
2
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(201 citation statements)
references
References 21 publications
6
191
2
2
Order By: Relevance
“…According to this model, MYC promotes tumorigenesis by facilitating translocations, deletions, and inversions throughout the genome (Mushinski and Mai, 2002), but does not cause elevated mutation rates (no hypermutability). Similar to our results with mouse BL, normal or near normal mutant rates in vivo were found in p53 7/7 thymic lymphomas (Buettner et al, 1996), polyoma middle T induced adenocarcinomas (Jakubczak et al, 1996), and Myc induced liver cancers (Davis et al, 1996). However, since in these studies the mutant rate was determined with the assistance of phage l assays that cannot detect chromosomal rearrangements, it is possible that the true mutant rate in these tumors was underreported.…”
supporting
confidence: 67%
“…According to this model, MYC promotes tumorigenesis by facilitating translocations, deletions, and inversions throughout the genome (Mushinski and Mai, 2002), but does not cause elevated mutation rates (no hypermutability). Similar to our results with mouse BL, normal or near normal mutant rates in vivo were found in p53 7/7 thymic lymphomas (Buettner et al, 1996), polyoma middle T induced adenocarcinomas (Jakubczak et al, 1996), and Myc induced liver cancers (Davis et al, 1996). However, since in these studies the mutant rate was determined with the assistance of phage l assays that cannot detect chromosomal rearrangements, it is possible that the true mutant rate in these tumors was underreported.…”
supporting
confidence: 67%
“…Upon amplification, all plaques gave full-length PCR products, indicating that there were no large cII deletions. Approximately 80% of the samples sequenced contained detectable mutations in cII, all of which altered the amino acid sequence; the remainder were presumed to be mutations elsewhere in that enhances P R transcription (24,27). No sample was found to harbor more than one mutation in the cII gene.…”
Section: Erbb2͞bigmentioning
confidence: 99%
“…Mammary adenocarcinomas arising in multiparous ErbB2͞Big Blue bitransgenic mice between 14 and 25 months of age (mean age of 20.8 months) were subjected to mutational analysis using a now well-used transgenic shuttle phage assay that selects for phage containing forward mutations in the cII gene (24). Mammary glands from female mice of an identical FVB͞N ϫ C57BL͞6 F 1 genetic background harboring the transgene alone failed to develop tumors and served as control tissue.…”
Section: Erbb2͞bigmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study of this kind found no increase in the number of mutant lacI transgenes rescued from thymic tumors (43). However, two of three subsequent transgene rescue studies detected increased mutation (34,44,45). For example, a recent study reported that 5-fold more mutant lacZ transgenes were rescued from pristaneinduced mouse plasmacytomas than from normal splenocytes (45).…”
Section: Discussionmentioning
confidence: 99%